Customised hybrid CT-MRI 3D-printed model for grade V spondylolisthesis in an adolescent. Issue 3 (1st March 2021) - Parthasarathy, Jayanthi; Sribnick, Eric A; Ho, Mai-Lan; Beebe, Allan
Abstract : 3D-printed patient-specific models provide added value for initial clinical diagnosis, preoperative surgical and implant planning and patient and trainee education. 3D spine models are usually designed using CT data, due to the ability to rapidly image osseous structures with high spatial resolution. Combining CT and MRI to derive a composite model of bony and neurological anatomy can potentially provide even more useful information for complex cases. We describe such a case involving an adolescent with a grade V spondylolisthesis in which a composite model was manufactured for preoperative and intraoperative evaluation and guidance. We provide a detailed workflow for creating such models and outline their potential benefit in guiding a multidisciplinary team approach.